A manual for economic and functional classification of government transactions - United National Bureau of Economic Affairs (New York : Dept. of Economic and Social Affairs, United Nations, 1958)
This manual presents two classification schemes, which are designed to provide meaningful data on government transactions - data essential to making economic and social policy
Includes index.
osc 11/06/2018
Loans
Keywords: Finance, Public